1967
DOI: 10.1111/j.1751-1097.1967.tb08803.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhibitors and Uncouplers of Photosynthetic Phosphorylation on the Delayed Light Emission of Chloroplasts*

Abstract: Measurements were made of the 3.7 msec delayed light emission of chloroplasts treated with a variety of agents which affect the rate of electron transport (Hill reaction) or photosynthetic phosphorylation. The presence of the electron acceptors ferricyanide or pyocyanine increased delayed light emission. Inhibitors of electron transport (3-(3,4dichloro-pheny1)-1, -I-dimethylurea or l,lO(ortho)-penanthroline) inhibited delayed light emission. Uncouplers of photosynthetic phosphorylation caused a decrease in del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…It has been reported previously that in the presence of phosphorylating reagents the extent of DLE is diminished (17 (Fig. 7).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been reported previously that in the presence of phosphorylating reagents the extent of DLE is diminished (17 (Fig. 7).…”
Section: Discussionsupporting
confidence: 62%
“…Several uncouplers were shown previously to inhibit DLE (17). Upon the addition of gramicidin, we have observed that the extent of "discharge" of the signal by subsequent addition of ADP decreased with increasing concentrations of the uncoupler.…”
Section: Effectssupporting
confidence: 50%
“…Mayne and Clayton (1967) examined the effects of a variety of electron transport and phosphorylation inhibitors and phosphorylation uncouplers on DLE and found that, under a variety of conditions, the intensity of DLE mirrored the predicted magnitude of the so-called high-energy phosphorylation intermediate. DLE increased when Hill reaction electron acceptors were added, and was inhibited by PSII inhibitors such as DCMU [3-(3,4-dichlorophenyl) 1,1 dimethylurea] and by phosphorylation uncouplers.…”
Section: Berger Mayne's Initial Research At the Kettering Laboratorymentioning
confidence: 99%
“…This ''proton gradient'' would be the concentration part of the protonmotive force (pmf) postulated to be the ''high energy intermediate'' in Peter Mitchell's chemiosmotic hypothesis (Mitchell 1961). Mayne and Clayton (1967) reasoned that if the high energy intermediate were the precursor of delayed fluorescence, and if it could be generated by an acid-base transition, it should be possible to produce light emission by an acid-base transition-in effect a reversal of the light-driven formation of the proton gradient. They subjected chloroplasts to a similar acid-base transition in front of a photomultiplier, and found that a burst of light was indeed emitted when the base was injected (Mayne 1966;Mayne and Clayton 1966).…”
Section: Berger Mayne's Initial Research At the Kettering Laboratorymentioning
confidence: 99%
“…It has become clear from the work of Mayne [2,3] and subsequent workers [4,5] that the high-energy state of phosphorylation acts on this back reaction. This effect is most readily observed in the 1 msec region of the decay.…”
Section: Introductionmentioning
confidence: 99%